Direct and indirect effects of pathogenic bacteria on the integrity of intestinal barrier - Lin-Zhen Shu; Yi-Dan Ding; Qing-Ming Xue; Wei Cai; Huan Deng (Therapeutic Advances in Gastroenterology, 2023)
Bacterial translocation is a pathological process involving migration of pathogenic bacteria across the intestinal barrier to enter the systemic circulation and gain access to distant organs. This phenomenon has been linked to a diverse range of diseases including inflammatory bowel disease, pancreatitis, and cancer. The intestinal barrier is an innate structure that maintains intestinal homeostasis. Pathogenic infections and dysbiosis can disrupt the integrity of the intestinal barrier, increasing its permeability, and thereby facilitating pathogen translocation. As translocation represents an essential step in pathogenesis, a clear understanding of how barrier integrity is disrupted and how this disruption facilitates bacterial translocation could identify new routes to effective prophylaxis and therapy. In this comprehensive review, we provide an in-depth analysis of bacterial translocation and intestinal barrier function. We discuss currently understood mechanisms of bacterial–enterocyte interactions, with a focus on tight junctions and endocytosis. We also discuss the emerging concept of bidirectional communication between the intestinal microbiota and other body systems. The intestinal tract has established ‘axes’ with various organs. Among our regulatory systems, the nervous, immune, and endocrine systems have been shown to play pivotal roles in barrier regulation. A mechanistic understanding of intestinal barrier regulation is crucial for the development of personalized management strategies for patients with bacterial translocation-related disorders. Advancing our knowledge of barrier regulation will pave the way for future research in this field and novel clinical intervention strategies.